Natural ventilation provisions in terraced-house designs in hot-humid climates: case of Putrajaya, Malaysia - Idowu, Ibiyeye Aminat; Ja'afar, Mohamad Fakri Zaky; Shari, Zalina (Universiti Putra Malaysia Press, 2015)
Due to the high risk of global warming from the increased level of energy consumption, energy sustainability is increasingly practised around the world especially in the residential sector. Attempts to save energy in hot-humid climates however, are mainly through improved mechanical cooling. Consequently, residential buildings are built to be air tight and they are provided with insufficient opening areas for natural ventilation which in turn, results in the deterioration of indoor air quality (IAQ). Previous studies on IAQ with respect to ventilation rates are mostly on indoor concentrations of contaminants and various diseases associated with them. Detailed studies on openings and their impact on delivered ventilation rates are still limited, particularly in hot-humid climates. This study investigates natural ventilation provisions in different house design types in Putrajaya, Malaysia with respect to the Uniform Building By-Law (UBBL) governing them. Five terrace house design types were selected, of which two were found to be non-compliant with UBBL 10% window area requirement. Simulations were conducted using the Integrated Environment Solution (IES〈VE〉) software and the results reveal that house types complying with the UBBL requirements exhibit higher ventilation rates and a longer duration of leaving windows open is found to improve ventilation rates. This paper informs regulatory stakeholders, designers and clients of the residential building sector of the impact of open designs on occupants' health and the importance of UBBL compliance and enforcement. This study further emphasises the need for occupants to increase the duration of leaving windows open and to embrace night ventilation as a means of improving natural ventilation in their homes.